2014
DOI: 10.1371/journal.pone.0100862
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear MEK1 Sequesters PPARγ and Bisects MEK1/ERK Signaling: A Non-Canonical Pathway of Retinoic Acid Inhibition of Adipocyte Differentiation

Abstract: Uncontrolled adipogenesis and adipocyte proliferation have been connected to human comorbidities. Retinoic acid (RA) is known to inhibit adipocyte differentiation, however the underlying mechanisms have not been adequately understood. This study reports that RA acting as a ligand to RA receptors (RARs and RXRs) is not a sine qua non to the inhibition of adipogenesis. Our intriguing observation of a negative correlation between increased retinoylation and adipogenesis led us to explore retinoylated proteins in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 72 publications
1
10
0
1
Order By: Relevance
“…RA also induces the nuclear enrichment of MEK1, which physically sequesters PPARγ from its target genes [32]. In the current study, we found that the RAR agonists inhibited the expression of adipogenic marker genes C/EBPα, PPARγ, and FABP4 during adipogenic differentiation at seven days in hBMSCs and SW872 cells, but the expression of C/EBPβ was increased.…”
Section: Discussionsupporting
confidence: 50%
“…RA also induces the nuclear enrichment of MEK1, which physically sequesters PPARγ from its target genes [32]. In the current study, we found that the RAR agonists inhibited the expression of adipogenic marker genes C/EBPα, PPARγ, and FABP4 during adipogenic differentiation at seven days in hBMSCs and SW872 cells, but the expression of C/EBPβ was increased.…”
Section: Discussionsupporting
confidence: 50%
“…Interestingly, MEK1 was recently described to have important roles in T cell transcriptional responses through regulation of the nuclear receptor corepressor silencing mediator of retinoid and thyroid hormone (SMRT) at the promoter of c-Fos (39). In addition, there have been reports describing the interactions between PPAR-γ and the activation of MEK1/2-ERK1/2 (40), and MEK1 itself can play a role in regulating nuclear localization and activation of PPAR-γ (41)(42)(43). PPARs have important roles in regulating macrophage responses to inflammation (44,45), and represents one of likely many potential mechanisms by which MEK1/2-ERK1/2 regulates macrophage responses.…”
Section: ) Erk1mentioning
confidence: 99%
“…Rich MEK1 in the nucleus decreases PPARγ availability and thus inhibits adipogenesis, while also disrupting the MEK1-ERK signaling cascade. 66 This shows that the molecular mechanisms underlying RA effects on adipocyte differentiation and adipogenesis are complex and remain poorly understood. Furthermore, it is proposed that there is a high turnover of adipocytes at all adult ages in humans.…”
Section: Pparγ Activation In Carotenoidinhibited Cancer-cell Prolifermentioning
confidence: 99%